2007
DOI: 10.4049/jimmunol.178.10.6476
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 Mediates Neuroinflammation and Neuronal Damage

Abstract: Innate immunity relies on pattern recognition receptors to detect the presence of infectious pathogens. In the case of Gram-positive bacteria, binding of bacterial lipopeptides to TLR2 is currently regarded as an important mechanism. In the present study, we used the synthetic bacterial lipopeptide Pam3CysSK4, a selective TLR2 agonist, to induce meningeal inflammation in rodents. In a 6-h rat model, intrathecal application of Pam3CysSK4 caused influx of leukocytes into the cerebrospinal fluid (CSF) and induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(110 citation statements)
references
References 46 publications
2
108
0
Order By: Relevance
“…In addition to its important roles in host defense in clearing bacteria, TLR2 may mediate some forms of inflammatory brain injury [42], including middle cerebral artery occlusion [43] and neonatal hypoxia-ischemiainduced brain injury [44]. Indeed, consistent with the known role of TLR2 in mediating neuroinflammation and neuronal damage [45], we have previously demonstrated that a single intraperitoneal injection of the TLR2 agonist Pam 3 CSK 4 revealed a robust increase in the WBC count in the CSF in mice on PND8 [38], and repeated administration of Pam 3 CSK 4 induced brain injury in newborn animals [19]. S. epidermidis bacteremia induced TLR2 expression in the brain in our current study ( Figure 5).…”
Section: Discussionmentioning
confidence: 59%
“…In addition to its important roles in host defense in clearing bacteria, TLR2 may mediate some forms of inflammatory brain injury [42], including middle cerebral artery occlusion [43] and neonatal hypoxia-ischemiainduced brain injury [44]. Indeed, consistent with the known role of TLR2 in mediating neuroinflammation and neuronal damage [45], we have previously demonstrated that a single intraperitoneal injection of the TLR2 agonist Pam 3 CSK 4 revealed a robust increase in the WBC count in the CSF in mice on PND8 [38], and repeated administration of Pam 3 CSK 4 induced brain injury in newborn animals [19]. S. epidermidis bacteremia induced TLR2 expression in the brain in our current study ( Figure 5).…”
Section: Discussionmentioning
confidence: 59%
“…TLR2 recognizes many pathogen-derived molecules and is expressed in the CNS by glial cells (microglia, astrocytes, oligodendrocytes) and neurons (24). TLR2 agonists initiate a proinflammatory response by microglia (25) and can induce microglial-mediated neuronal death in primary neural cultures (26,27) and in vivo (28). We hypothesize the VLC-LPS species that accumulate following ABHD12 disruption could serve as endogenous TLR2 ligands, leading to microglial activation and neuroinflammation in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal injection into mice and analysis of the cerebrospinal fluid was performed as described previously (30). Ten micrograms of RNA was used for injections.…”
Section: Intrathecal Injection Into Micementioning
confidence: 99%